Effect of La0.6Sr0.4Co0.3Fe0.8O3-δ air electrode-electrolyte interface on the short-term stability under high-current electrolysis in solid oxide electrolyzer cells - Pan, Zehua (2020)
In this work, the effects of the La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF) electrode–yttria stabilized zirconia (YSZ) electrolyte interface on the stability of LSCF electrodes under high-current electrolysis are studied. Six different half-cells with different configurations are tested at 800 °C for 264 h under an electrolysis current of 1 A cm−2. A few concluding remarks can be drawn by comparing the behaviors of different cells. Firstly, it is confirmed that the formation of SrZrO3 at the interface will lead to the delamination of air electrode. Thus, the formation of SrZrO3 should be strictly prevented. Secondly, increasing sintering temperature can decrease the degradation rate of polarization resistance, RP, for LSCF electrodes. Thirdly, the increase of ohmic resistance, RS, comes from structural changes as the degradation rate in percentage is similar for cells with different electrolytes and electrodes. Fourthly, the LSCF electrode after the electrolysis test shows recrystallization and lattice shrink which could be the reason for the degradation of LSCF electrodes on Gd0.1Ce0.9O2–δ (GDC) electrolytes. Lastly, comparing all the samples, the cell composed of YSZ electrolyte, dense GDC interlayer and LSCF electrode sintered at 1000 °C can be used for future study on the degradation mechanisms of the LSCF air electrode and the electrolyte.